Fermentasi Whey Keju Menggunakan Biji Kefir (Kefir Grains) dengan Variasi Sumber Nitrogen - Rohula Utami; Edhi Nurhartadi; Asri Nursiwi; Martina Andriani (agriTECH, 2017)
Cheese whey is a waste product in cheese processing which contains 4–5% of lactose. Having high carbon source, this material could be a potential  fermentation medium for kefir grains. During fermentation of kefir grains, alcohol, lactic acid and exopolysaccharide (kefiran) were produced. The kefir grains fermentation also affected by nitrogen source. Therefore, effects of different composition of lactose and nitrogen sources (including yeast extract, urea and mung bean sprouts extract)  in the fermentation were examined in this study. The results showed that after 24 hours of incubation, kefir grains biomass reached 21.30-27.15 g (dry wt, g/250mL medium) from 25 g of intial kefir grains biomass. Fermentation broth showed pH values ranged from 3.49–3.94; alcohol level ranged from 0.11-0.31%; and lactic acid content ranged from 0.49–1.47%. The total of kefiran extracted from kefir grain and fermentation broth ranged from 0.63-1.76 g/L. This study indicated that cheese whey can be used as fermentation medium to produce alcohol, lactic acid and kefiran by kefir grains. The highest production of kefiran was achieved in the medium containing 1.2% of whey lactose and 4% of mung bean sprouts extract.Cheese whey is a waste product from cheese processing industry which still has lactose content of 4-5%, so that it can be used as a carbon source in the fermentation medium of kefir grains. During fermentation of kefir grains, alcohol, lactic acid and exopolysaccharide commonly called as kefiran were produced. The kefir grains fermentation also affected by nitrogen source. Furthermore, fermentation medium composition were varied at whey lactose concentration and nitrogen source composition (yeast extract, urea and mung bean sprouts extract) for kefir grains fermentation. The results showed that after 24 hours fermentation, kefir grains biomass ranged from 21.30-27.15 g; pH values ranged from 3.49-3.94; alcohol level ranged from 0.11-0.31%; lactic acid content ranged from 0.49-1.47%; and the total of kefiran ranged from 0.63-1.76 g/L. Fermentation medium composition that produced the higher total of kefiran was 1,2% whey lactose and 4% mung bean sprouts extract as nitrogen source. ABSTRAKWhey keju adalah produk sampingan dari industri pengolahan keju yang masih memiliki kandungan laktosa sebesar 4–5% sehingga dapat dimanfaatkan sebagai sumber karbon pada media fermentasi oleh biji kefir. Selama proses fermentasi menggunakan biji kefir terjadi pembentukan alkohol, asam laktat dan eksopolisakarida (kefiran). Sumber nitrogen juga dapat mempengaruhi proses fermentasi. Oleh karena itu, dalam penelitian ini dilakukan variasi perlakuan, yaitu variasi konsentrasi laktosa pada whey dan variasi komposisi sumber nitrogen (yeast extract, urea dan ekstrak tauge kacang hijau) sebagai media fermentasi oleh biji kefir. Setelah fermentasi biji kefir selama 24 jam, jumlah biomassa biji kefir berkisar antara 21,30–27,15 g (berat kering g/250 mL medium fermentasi) dari jumlah biomassa awal 25 g. Cairan fermentasi menunjukkan nilai pH berkisar antara 3,49–3,94; kadar alkohol berkisar antara 0,11–0,31% dan kadar asam laktat berkisar antara 0,49–1,47%. Total rendemen kefiran yang didapatkan dari ekstraksi biji kefir dan cairan fermentasi berkisar antara 0,63–1,76 g/L.  Hasil penelitian ini mengindikasikan bahwa whey keju dengan penambahan sumber nitrogen dapat digunakan sebagai medium fermentasi oleh biji kefir untuk menghasilkan metabolit berupa alkohol, asam laktat dan kefiran. Variasi formulasi media fermentasi yang menghasilkan kefiran dalam jumlah tertinggi adalah penggunaan konsentrasi laktosa whey keju 1,2% dan sumber nitrogen dari ekstrak tauge kacang hijau sebesar 4%.